Komunikasi Kelompok Tim Kreatif Dalam Pengambilan Keputusan Pada Program INSERT PAGI di Trans TV - Ria Yunita (Jurnal Komunikasi, 2018)
Abstract  - Communication of the group of communications that takes place between members of a group as a face-to-face interaction of three or more individuals in order to obtain the intended purpose or objectives such as information sharing, self-maintenance or problem solving so that all members can accurately grow other members' personal characteristics. .Infotainment, packaging of the event wrapped and inserted entertainment to attract the attention of the audience. based on information, which also contains entertainment content to increase popularity. This study aims to know as well as learn and know the way of Communication Team Creative Team In Decision Making In Program Insert Morning Program at Trans TV station. "Creative Team Process Communication Process In Decision Making In Insert Morning Program at Trans TV station, explaining, Problem Formulation, Problem Analysis, Evaluating Alternative, Taking Alternative Decision. Keywords: Group Communication, Creative Team, Infotainment Program